Effects of Long Bones on Fetal Weight Estimation - Kaygusuz, Ikbal; Kosus, Aydin; Kosus, Nermin; Duran, Muzeyyen (Annals of Medical Research, 2021)
None
Keywords: Estimated Fetal Weight; Femur Length; Long Bones.